On measuring uncertainty and its impact on investment: Cross-country evidence from the euro area - Philipp Meinen; Oke Röhe (Deutsche Bundesbank, 2016)
Investment fell sharply in the euro area after the financial crisis and has not yet returned to pre-crisis levels in many core economies. Focusing on the four largest euro-area countries, this paper investigates the role of uncertainty for investment dynamics. By doing so, we compare five prominent uncertainty proxies put forward in the recent literature: the (implied) stock market volatility, a survey-derived measure of expectations dispersion, a newspaper-based indicator of policy uncertainty, and two indicators taking up the concept of (econometric) unpredictability. Although all uncertainty measures show countercyclical behavior, we find uncertainty as measured by the conditional volatility of the unforecastable components of a broad set of time series to exhibit noticeable robust effects across different model specifications and countries. Based on this type of uncertainty proxy, we document pronounced negative investment responses to uncertainty shocks. We further show that these effects can explain a relevant portion of the decrease in investment in the course of the Great Recession.
Keywords: C53; D81; E22; E32; 330; Uncertainty; Investment; Euro Area